A novel AI-AVO approach for maximum power generation of PMSG - S. Chinamalli, Prashant Kumar; Sasikala, Mungamuri (Institute of Advanced Engineering and Science, 2024)
Permanent magnet synchronous generators (PMSGs) are necessary for producing wind energy that is both highly reliable and reasonably priced. An inventive control technique for the driven interior PMSG (IPMSG) is presented here to maximize wind energy output and decrease losses. This research established an innovative optimization strategy for the highest wind power generation with reduced overall loss in PMSG-based Wind power generation systems. Considering, that the tip speed ratio (TPR), rotor speed ???????? , and quadrature axis current ???????? are optimized in the proposed work in such a way to enhance wind power generation. Further, the direct axis current ???????? is calculated from the optimized rotor speed ????????. The minimization of core loss is considered as the fitness function, which is a function of the direct current axis ????????and quadrature current axis ????????. The optimization is carried out using the explored aquila with African vulture optimization (EA-AVO) technique, which is the conceptual incorporation of prevailing techniques, like the aquila optimization algorithm (AOA) and the AVO algorithm. The performance of the proposed method is validated over the conventional methods, in terms of power output, losses, efficiency, and convergence analysis. According, the findings show that the proposed method attains less overall loss of 149.62 at the starting stage of 50 rotor speed, and it was 36.46% higher than AQO, 36.17% higher than AVOA, 36.59% higher than GOA methods 36.42%, and higher than WHO+PI approaches.